2012
DOI: 10.1007/s13280-012-0324-z
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainties in a Baltic Sea Food-Web Model Reveal Challenges for Future Projections

Abstract: Models that can project ecosystem dynamics under changing environmental conditions are in high demand. The application of such models, however, requires model validation together with analyses of model uncertainties, which are both often overlooked. We carried out a simplified model uncertainty and sensitivity analysis on an Ecopath with Ecosim food-web model of the Baltic Proper (BaltProWeb) and found the model sensitive to both variations in the input data of pre-identified key groups and environmental forci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 47 publications
1
25
0
Order By: Relevance
“…The Baltic Sea models applied in ECOSUPPORT are capable of simulating past climate variations and eutrophication since 1850, building confidence that the models are able to simulate future changes (e.g., Eilola et al 2011;Gustafsson et al 2012;Niiranen et al 2012;Ruoho-Airola et al 2012). In future climate, water temperatures are projected to increase and salinities are projected to decrease (due to the increased total freshwater supply), which is in accordance with earlier studies (e.g., Arheimer et al 2012;Meier et al 2012;Neumann et al 2012).…”
Section: Key Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…The Baltic Sea models applied in ECOSUPPORT are capable of simulating past climate variations and eutrophication since 1850, building confidence that the models are able to simulate future changes (e.g., Eilola et al 2011;Gustafsson et al 2012;Niiranen et al 2012;Ruoho-Airola et al 2012). In future climate, water temperatures are projected to increase and salinities are projected to decrease (due to the increased total freshwater supply), which is in accordance with earlier studies (e.g., Arheimer et al 2012;Meier et al 2012;Neumann et al 2012).…”
Section: Key Resultssupporting
confidence: 80%
“…Despite the high uncertainties involved, which are due to model shortcomings and unknown future scenarios of external nutrient loads, a basic conclusion seems to be that climate change can be expected to reinforce oxygen depletion, to increase phytoplankton biomass, and to reduce water transparency and biodiversity (due to decreased salinity) (e.g., Eilola et al 2012;Meier et al 2011bMeier et al , 2012Neumann et al 2012). Further, we found that in future climate, cod biomass may decrease and sprat biomass may increase assuming present day estimates of sustainable fishing (e.g., MacKenzie et al 2012;Niiranen et al 2012). However, all food web and fish population models indicate that the level of cod fishery is important for determining the cod stock size also in the future, independent of the climate scenario used.…”
Section: Key Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…While the importance of global sensitivity analysis is recognised, and despite their known limitations, only local sensitivity methods have been attempted (e.g. Köhler and Wirtz, 2002;Niiranen et al, 2012).…”
Section: Environmental Protection Agency 2009)mentioning
confidence: 99%
“…While climate change effects on species' distributions and abundance is a known uncertainty [7 -9], how climate change will disturb harvested species' growth rates is often overlooked [10][11][12]. Ignoring this latter type of uncertainty may have detrimental consequences such as eventual stock collapse [12,13]. Hence, finding management strategies that can handle uncertainty in species' changing growth in addition to determining abundance is a very pertinent resource management problem.…”
Section: Introductionmentioning
confidence: 99%